2018
DOI: 10.1002/anie.201812550
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic and Scalable Syntheses of Unsymmetrical 1,2,4,5‐Tetrazines by Thiol‐Containing Promotors

Abstract: Despite the growing application of tetrazine bioorthogonal chemistry,itisstill challenging to access tetrazines conveniently from easily available materials.Described here is the de novo formation of tetrazine from nitriles and hydrazine hydrate using ab road array of thiol-containing catalysts, including peptides.Using this facile methodology,the syntheses of 14 unsymmetric tetrazines,c ontaining ar ange of reactive functional groups,o nt he gram scale were achieved with satisfactory yields.U sing tetrazine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Dodecanal and farnesol were purchased from commercial sources and used without further purification. Hexanal [60], undecanal [61], tridecanal [62], octadecanal [63], and 2,5,8,11-tetraoxatridecan-13-al [64] all were obtained by oxidation of the corresponding primary alcohol and exhibited characterization consistent with the published literature. Final purity assessments were made based on an analytical RP-HPLC-MS system from Agilent Technologies Inc. (Santa Clara, CA, USA) using the following columns and conditions: Phenomenex Synergi Polar-RP (Phenomenex, Torrance, CA, USA), 4,6 mm × 150 mm, 4 µm, UV detection (Agilent Technologies Inc., Santa Clara, CA, USA) at 250 nm or 280 nm, 5–50% MeCN with 0.1% formic acid (FA) in water (0.1% FA) over 20 min at 0.5 mL/min, or 30–90% MeOH (0.1% FA) in water (0.1% FA) over 20 min at 0.5 mL/min; Phenomenex C18 4.6 mm × 50 mm, 4 µM, UV detection at 280 nm, 10–90% MeCN (0.1% FA) in water (0.1% FA) over 15 min at 0.5 mL/min, or 10–90% MeOH (0.1% FA) in water (0.1% FA) over 15 min at 0.5 mL/min.…”
Section: Methodssupporting
confidence: 54%
“…Dodecanal and farnesol were purchased from commercial sources and used without further purification. Hexanal [60], undecanal [61], tridecanal [62], octadecanal [63], and 2,5,8,11-tetraoxatridecan-13-al [64] all were obtained by oxidation of the corresponding primary alcohol and exhibited characterization consistent with the published literature. Final purity assessments were made based on an analytical RP-HPLC-MS system from Agilent Technologies Inc. (Santa Clara, CA, USA) using the following columns and conditions: Phenomenex Synergi Polar-RP (Phenomenex, Torrance, CA, USA), 4,6 mm × 150 mm, 4 µm, UV detection (Agilent Technologies Inc., Santa Clara, CA, USA) at 250 nm or 280 nm, 5–50% MeCN with 0.1% formic acid (FA) in water (0.1% FA) over 20 min at 0.5 mL/min, or 30–90% MeOH (0.1% FA) in water (0.1% FA) over 20 min at 0.5 mL/min; Phenomenex C18 4.6 mm × 50 mm, 4 µM, UV detection at 280 nm, 10–90% MeCN (0.1% FA) in water (0.1% FA) over 15 min at 0.5 mL/min, or 10–90% MeOH (0.1% FA) in water (0.1% FA) over 15 min at 0.5 mL/min.…”
Section: Methodssupporting
confidence: 54%
“…We first constructed the cyanine‐like probe 1 containing a polymethine conjugated system, using our recently reported Horner–Wadsworth–Emmons reaction for tetrazine derivatization (Table 1). [20] In this probe, the para ‐dimethylaniline acts as the donor, while the hydroxyl group at the 3‐position of tetrazine improves solubility with neutral charge. Probe 1 , which emits no detectable fluorescence, reacted nearly quantitatively with bicyclooctyne (BCN) 6 (Supporting Information, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrazine is a good reductant and a good nucleophile; thus, the reactions it is employed in usually offer poor substrate scopes and harsh conditions [ 14 ]. To overcome these limitations, organocatalytic approaches for the preparation of unsymmetrical tetrazines were developed by Wu et al in 2019 ( Scheme 1 d) [ 18 ]. It was suggested that a thiol-containing organocatalyst could promote the formation of unsymmetrical tetrazines at room temperature from hydrazine hydrate and nitriles bearing reactive functional groups.…”
Section: Synthesis Of Tetrazinesmentioning
confidence: 99%